UPAYA DALAM PENERAPAN KLAUSULA EKSONERASI DALAM PERJANJIAN JUAL BELI BARANG AGAR SEIMBANG - Yasinta Karmelia U.lulu (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACTThe clause eksoneri In business practice in Indonesia often found an agreement made with the provisions of the Code beyond the Civil Code that the provisions as sayarat called Clause Eksoneri or clause penyampingan this often creates problems because it is very detrimental to the buyer on the intent of the clause umumnya.Adapun eksoneri or penyampingan this clause is to limit the liability of either party, usually the seller, in this case the seller of electronic goods. With clause eksoneri he limit his responsibility and imposes a duty on the buyer or by the words generally stronger party imposes a duty on the weaker side. The Steps - Steps to be taken in order to clause seimbang.Apabila Eksoneri be considered, then the clause in the agreement eksoneri sometimes too one-sided, to the detriment of the other party. To overcome this particular measures should be taken in order to avoid overly burdensome aklibat weak. Steps - steps are as follows: Subject to the provisions of Law - laws that are governing the rights and obligations based on good faith; Writing eksoneri clause (clause penyampingan) was made in a clear and easy to read, by every person who wants an agreement by the parties; Eksoneri clause (clause penyampingan) may not be the basic condition (Condition); eksoneri clause (clause penyampingan) load to bear joint liability arising as a result of the agreement, for example, if there is damage to the purchased goods, then the seller to bear the cost.